2021
DOI: 10.1155/2021/5574202
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum Polysaccharide Ameliorates Heat-Stress-Induced Impairment of Primary Sertoli Cells and the Blood-Testis Barrier in Rat via Androgen Receptor and Akt Phosphorylation

Abstract: Male infertility induced by heat stress has been attracting more and more attention. Heat stress not only causes apoptosis of spermatocytes but also has adverse effects on Sertoli cells, further damaging spermatogenesis. Lycium barbarum polysaccharide (LBP) is the main bioactive component of Lycium barbarum, which has a protective effect on male reproduction, but its mechanism is still unclear. In this study, our results proved that LBP blocked the inhibitory effect on the proliferation activity of Sertoli cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Increased apoptosis may have negative consequences on sperm production, ultimately jeopardizing male fertility ( Zhang et al, 2019 ). Some antioxidant-rich natural substances, such as morin ( Arisha et al, 2019 ), luteolin, and Lycium barbarum polysaccharide ( Hu et al, 2021 ), also have anti-apoptotic properties, minimizing damage to the BTB. Antioxidant supplementation may be a potentially viable treatment method for both the prevention and relief of BTB damage, according to evidence from these animal investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Increased apoptosis may have negative consequences on sperm production, ultimately jeopardizing male fertility ( Zhang et al, 2019 ). Some antioxidant-rich natural substances, such as morin ( Arisha et al, 2019 ), luteolin, and Lycium barbarum polysaccharide ( Hu et al, 2021 ), also have anti-apoptotic properties, minimizing damage to the BTB. Antioxidant supplementation may be a potentially viable treatment method for both the prevention and relief of BTB damage, according to evidence from these animal investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of HaCaT cell injury induced by PM2.5, it was found that LBP could reduce apoptosis, inhibit the expression of GRP78 and CHOP, reduce the transformation of LC3I to LC3II, inhibit Bax protein, and activate Bcl-2 protein. 63 In this study, the apoptosis rate of testes and epididymis in 2,4-D + LBP group was lower than that in 2,4-D group, and the expression of apoptosis-related genes in testicular tissue of 2,4-D + LBP group was lower than that in 2,4-D group. These results suggest that LBP can reduce the apoptosis of testicular cells induced by 2,4-D, and its mechanism may be related to the inhibition of Fas/FasL signal pathway.…”
Section: Discussionmentioning
confidence: 45%
“…It has been found that LBP can reduce the expression of HIF1‐α and Bcl2 in human trophoblast cells exposed to H 2 O 2 , and reduce the expression of Bax, thus inhibiting apoptosis and oxidative stress. In the study of HaCaT cell injury induced by PM2.5, it was found that LBP could reduce apoptosis, inhibit the expression of GRP78 and CHOP, reduce the transformation of LC3I to LC3II, inhibit Bax protein, and activate Bcl‐2 protein 63 . In this study, the apoptosis rate of testes and epididymis in 2,4‐D + LBP group was lower than that in 2,4‐D group, and the expression of apoptosis‐related genes in testicular tissue of 2,4‐D + LBP group was lower than that in 2,4‐D group.…”
Section: Discussionmentioning
confidence: 99%
“…SCs and BTB may not be able to provide su cient nutrients and a safe environment for spermatogenesis if their structure or function was destroyed, resulting in abnormal spermatogenesis or survival, leading to infertility. High temperature is a common cause of structural and functional damage to SCs and BTB, and a 43°C water bath is usually used to establish a testicular heat stress model [23][24].…”
Section: Discussionmentioning
confidence: 99%